Consumers’ demand and willingness to pay for rice attributes in Malaysia - Abdul Hadi, Ahmad Hanis Izani; Selamat, Jinap; Shamsudin, Mad Nasir; Radam, Alias; Abdul Karim, Muhammad Shahrim (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
The growth of the Malaysian’s per capita income has generally empowered consumers to have more choices for food, more purchasing power, health consciousness and demand for more nutritional values of their food intake. Motivated by the changes in Malaysian consumer’s food choice, a conjoint analysis was performed to investigate Malaysian consumers’ demand for rice attributes and how much consumers are willing to pay for the demanded attribute. A conjoint analysis is a method used in identifying and understanding the combined effects of product attributes on preferences for a product or service. In conjoint analysis, utility is the conceptual basis for assessing the value of a product or service, where individuals make decisions between bundles of products based on their budget constraints. The findings suggested that the most important attribute for rice was food safety, followed by taste and size of grain. Consumers were also willing to pay premium prices for the demanded attributes. The findings would have positive implications for the agrifood industry if it responds effectively to translate into business opportunities to these changes.